Assessing aesthetic outcomes of different incision types for nipple-sparing mastectomy followed by radiation therapy in prepectoral direct-to-implant breast reconstruction: a retrospective study - Jae Hoon Jeong; Ha Eun Park; Eun-Kyu Kim; Chan Yeong Heo; Chongsoo Park (World Journal of Surgical Oncology)
Abstract Background This study analyzes the aesthetic outcomes associated with inframammary fold (IMF) incisions compared to radial incisions, with or without a periareolar component (referred to as periareolar/radial, PR), considering nipple-sparing mastectomy (NSM) followed by prepectoral direct-to-implant (DTI) reconstruction and subsequent post-mastectomy radiotherapy (PMRT). We assessed changes in breast and nipple symmetry, nipple-to-IMF distance, and nipple Y-axis coefficients to understand how different incisions influence post-radiation aesthetic outcomes. Methods Forty patients who underwent NSM and prepectoral DTI reconstruction followed by PMRT between September 2019 and December 2022 in a single institution were included. Patients were divided into PR incision (n = 9) and IMF incision (n = 31) groups, with the latter further separated into IMF 1 group (surgeries from 2019 to 2021, n = 13) and IMF 2 group (surgeries in 2022, n = 18). Pre- and postoperative (6–18 months after surgery) analyses of body measurements and medical photographs were conducted using the Seoul Breast Esthetic Scoring Tool (S-BEST) software, developed by same institution, to calculate breast symmetry scores, nipple-to-IMF distance, and nipple Y-axis coefficients. Statistical analyses assessed differences between groups. Results All groups showed decreased breast symmetry scores postoperatively (PR group: -1.111, IMF 1 group: -0.539, IMF 2 group: -0.389) and increased nipple-to-IMF distance (PR group: 0–0.2 cm, IMF 1 group: 0.2–0.5 cm, IMF 2 group: 0.3–0.4 cm). The changes in nipple y-axis coefficients were minimal across all groups. And the PR group received a lower average radiation dose (47.64 ± 5.2 Gy) than IMF 1 group (54.45 ± 5.28 Gy) and IMF 2 group (54.07 ± 4.79 Gy). Statistical analysis indicated no significant differences across the groups (p > 0.05, Kruskal-Wallis test). Conclusions While IMF and PR incisions yielded similar aesthetic outcomes post-radiation, IMF incisions showed trends toward better symmetry, especially at higher radiation doses. These findings support the IMF incision as a favorable choice in NSM with DTI reconstruction followed by PMRT, though patient anatomy and preferences remain critical for surgical planning.